Ultra-weak sector, Higgs boson mass, and the dilaton - Kyle Allison (Physics Letters B, 2014)
The Higgs boson mass may arise from a portal coupling to a singlet field σ which has a very large VEV f≫mHiggs. This requires a sector of “ultra-weak” couplings ζi, where ζi≲mHiggs2/f2. Ultra-weak couplings are technically naturally small due to a custodial shift symmetry of σ in the ζi→0 limit. The singlet field σ has properties similar to a pseudo-dilaton. We engineer explicit breaking of scale invariance in the ultra-weak sector via a Coleman–Weinberg potential, which requires hierarchies amongst the ultra-weak couplings.